2003
DOI: 10.1159/000071955
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the Hippocampus of an Adult Marsupial

Abstract: In the adult eutherian brain, stem cells in the dentate gyrus continually divide throughout adult life and into old age producing new granule cells. However, it was not known whether this is also the case for marsupials. Previously, in fact, it was thought that marsupials did not have continued neurogenesis in the mature brain. Here we examined neurogenesis in the adult brain of a small marsupial, the fat-tailed dunnart, using 3H-thymidine to label newly generated cells. We showed that neurogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Therefore, one of the most conspicuous features of adult neurogenesis in mammals is that it is confined to two brain regions (Lledo et al 2006): (1) the subventricular zone, where new interneurons are born that travel the rostral migratory stream to the olfactory bulb, and (2) in the hippocampus, in the subgranular zone of the DG, where new principal cells, dentate GCs, are generated. This restricted distribution has been seen in every mammalian genus studied, including marsupials (Harman et al 2003;Grabiec et al 2009), indicative of this pattern having been established early in the phylogeny of mammals.…”
mentioning
confidence: 77%
“…Therefore, one of the most conspicuous features of adult neurogenesis in mammals is that it is confined to two brain regions (Lledo et al 2006): (1) the subventricular zone, where new interneurons are born that travel the rostral migratory stream to the olfactory bulb, and (2) in the hippocampus, in the subgranular zone of the DG, where new principal cells, dentate GCs, are generated. This restricted distribution has been seen in every mammalian genus studied, including marsupials (Harman et al 2003;Grabiec et al 2009), indicative of this pattern having been established early in the phylogeny of mammals.…”
mentioning
confidence: 77%
“…Again, lower rates of neurogenesis were found in hedgehogs than in moles. In the majority of species examined, adult neurogenesis in the DG persists throughout life, although it declines with age, which is a common feature in all mammalian species [Kuhn et al, 1996;Eriksson et al, 1998;Harman et al, 2003;Maslov et al, 2004;Leuner et al, 2007;Grabiec et al, 2009]. It has been reported that rats significantly decreased the number of cells generated in the DG before their midlife but afterwards the rate of neurogenesis in their DG remained at the same level throughout the rest of their life [Kuhn et al, 1996].…”
Section: Neurogenesis In the Dg Of Wild Animalsmentioning
confidence: 97%
“…Adult neurogenesis has been studied in about twenty mammalian species: rodents [Galea and McEwen, 1999;Lavenex et al, 2000;Parent et al, 2002;Amrein et al, 2004;Barker et al, 2005], shrews [Bartkowska et al, 2008], bats [Amrein et al, 2007], carnivores [Hwang et al, 2007;Pekcec et al, 2008], primates including humans [Eriksson et al, 1998;Gould et al, 1999;Kornack and Rakic, 1999;Bernier et al, 2002] and marsupials [Harman et al, 2003;Grabiec et al, 2009]. In the majority of these species, new DG neurons are generated throughout life, but the rate of neurogenesis decreases sharply at young adult age to stabilize at much lower levels for the rest of their life [Maslov et al, 2004;Hwang et al, 2007;Grabiec et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest is that, in shrews, AHN is literally switched off after the first winter and remains off for the remainder of the animal's life. In marsupials of the Australian region, AHN has been shown in the laboratory-bred mouse-like fat-tailed dunnart (Sminthopsis crassicaudata, order Dasyuromorphia) based on 3 H-thymidine incorporation and immunohistochemistry for GFAP, PSA-NCAM, and calbindin (Harman et al 2003). AHN has also been shown in an American marsupial (order Didelphimorphia), the laboratory-bred gray short-tailed opossum (Monodelphis domestica), using BrdU in combination with NeuN, DCX, and GFAP (Grabiec et al 2009).…”
Section: Evidence Of Hippocampal Neurogenesis In Other Wild and Domesmentioning
confidence: 99%